A Brief Overview on BDNF-Trk Pathway in the Nervous System: A Potential Biomarker or Possible Target in Treatment of Multiple Sclerosis? - Schirò, Giuseppe; Iacono, Salvatore; Ragonese, Paolo; Aridon, Paolo; Salemi, Giuseppe; Balistreri, Carmela Rita (Frontiers in Neurology, 2022)
The growing incidence of neurodegenerative disorders in our populations is leading the research to identify potential biomarkers and targets for facilitating their early management and treatments. Biomarkers represent the crucial indicators of both physiological and pathological processes. Specific changes in molecular and cellular mechanisms of physiological processes result in biochemical alterations at systemic level, which can give us comprehensive information regarding the nature of any disease. In addition, any disease biomarker should be specific and reliable, able to consent of distinguishing the physiological condition of a tissue, organ, or system from disease, and be diverse among the various diseases, or subgroups or phenotypes of them. Accordingly, biomarkers can predict chances for diseases, facilitate their early diagnosis, and set guidelines for the development of new therapies for treating diseases and disease-making process. Here, we focus our attention on brain neurotrophic factor (BDNF)–tropomyosin receptor kinase (Trk) pathway, describing its multiple roles in the maintenance of central nervous system (CNS) health, as well as its implication in the pathogenesis of multiple sclerosis (MS). In addition, we also evidence the features of such pathway, which make of it a potential MS biomarker and therapeutic target.